RELATIONS BETWEEN MUSTAFA KEMAL ATATURK AND UNIONISTS (during the armistice period 1918-1921) - Kilinchkaya, Mehmet Dervish (Journal of history, 2017)
Turkish historiography, studies and works which evaluate the period of National Struggle is usually tend to be shaped by the Speech by Mustafa Kemal Ataturk. As it is clear from the information given up to this point, following the military coup of 1913, the Committee of Union and Progress had formed a serious political and social domination (or reign) over the society and started to take some precautions in order to prevent the dissolution of the state. As a whole, the power and the prevalence of the Committee of Union and Progress are based on this foundation of organization. We should also look at another issue which is the characteristic of the relationship between Mustafa Kemal Pasha and the Committee of Union and Progress. At this point, we should go back a little and try to unserstand the role and place of Mustafa Kemal Pasha within all these developments since the aforementioned balance of power, he had became the key factor. Yet, it is also clear that those who sympathize with the Committee and realized the importance of being a ‘citizen’ via this organization have gathered around Mustafa Kemal Pasha did this not just out of desperation but rather a necessary expression of their patriotism and public spirit.